Urbanization and Land Use Transformation in Ternate City: A Phenomenological Geography Perspective on Spatial and Environmental Change - Muhammad Ikhsan; Epon Ningrum; Mamat Ruhimat; Iwan Setiawan; Badrizal Al Hazar (Poltanesa, 2026)
Rapid urbanization in Ternate City has driven significant transformations in land use, creating new ecological and social challenges. This study aims to examine the impacts of urbanization on land use changes through the lens of geographical phenomenology, focusing on the subjective experiences of communities in response to spatial transformation. Employing a qualitative approach, data were collected through in-depth interviews, participatory observation, literature review, and spatial and statistical data from official agencies. The findings reveal a massive conversion of land from agricultural and ecological functions to residential and commercial zones, especially in coastal and suburban areas. Communities’ express ambivalence toward these changes experiencing a sense of loss for meaningful spaces while simultaneously striving to adapt to new conditions. The study also highlights a mismatch between spatial planning and actual land use, which exacerbates environmental degradation and social fragmentation. A phenomenological approach reveals the symbolic meanings of lost spaces and the transformation of community identity, which is often overlooked in conventional spatial analyses. This study recommends spatial planning policies that are more responsive to social and cultural dimensions within the framework of sustainable urban development.